2022
DOI: 10.3390/pharmaceutics14112391
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Diabetic Macular Edema Switched from Dexamethasone Intravitreal Implant to Fluocinolone Acetonide Intravitreal Implant

Abstract: To assess anatomical and functional outcomes after switching from dexamethasone implant (DEXi) to fluocinolone acetonide implant (FAci) in 113 diabetic macular edema eyes, a multicentric retrospective observational study was conducted. Seventy-five eyes (73.5%) were switched 1–8 weeks after their last DEXi. The mean best-corrected visual acuity improved to 59.8 letters at month 4 and remained stable during the follow-up. The mean central macular thickness (CMT) significantly decreased during the follow-up, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…The clinical efficacy of the Iluvien intravitreal insert has been demonstrated by other RCTs and several real-life observational studies [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ] and confirmed by systematic reviews, meta-analyses, and expert panels [ 142 , 143 , 144 ].…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 78%
See 3 more Smart Citations
“…The clinical efficacy of the Iluvien intravitreal insert has been demonstrated by other RCTs and several real-life observational studies [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ] and confirmed by systematic reviews, meta-analyses, and expert panels [ 142 , 143 , 144 ].…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 78%
“…Published studies with the FAc implant with at least 36 months of follow-up reported a VA gain ranging between 3.6 and 11 letters [ 40 , 85 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 99%
See 2 more Smart Citations
“…In this cohort, patients received FAi after a mean time of 5 months after the latest DEXi, which is longer than the 4- to 8-week interval that the French Uveitis Network currently recommends (data not published). In fact, it has been shown elsewhere that the best functional and anatomical results are reached faster in patients injected with FAi at the time of DEXi peak of action (i.e., around 4–8 weeks) [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%